International economics - Gerber, James (Hoboken : Pearson, 2014)
"International Economics is designed for a one-semester course covering both the trade and finance components of international economics. The Eighth Edition continues the approach of the first seven editions by offering a principles-level introduction to the core theories together with policy analysis and the institutional and historical contexts of international economic relations. My goal is to make economic reasoning about the international economy accessible to a diverse group of students, including both economics majors and nonmajors. My intention is to present the consensus of economic opinion, when one exists, and to describe the differences when one does not. In general, however, economists are more often in agreement than not"--
Includes index.
Keywords: International economic relations; International economic integration; International trade; Commercial policy; United States -- Foreign economic relations